Age and forming conditions of groundwater in the middle Pliocene aquifer in the Mekong Delta, Vietnam, based on the results of carbon radioactive isotope study - Hoang Quoc Viet Lam; A. B. Lisenkov; V. J. Lavrushin; K. V. Belov (Известия высших учебных заведений: Геология и разведка, 2019)
The results of studying and assessment of the impact of climate change on the groundwater in the Mekong delta have indicated that the exploitation of quaternary aquifers is not enough to solve the task of water supply in the region. Therefore, in the exploitation plan of groundwater in the Mekong Delta, the greatest prospects are bound with Pliocene aquifers. So, by using of carbon radioactive isotope to determine the age and forming conditions of groundwater in the middle Pliocene aquifer in the Mekong Delta, the important information for planning exploitation and zoning of areas subject to restrained exploitation of groundwater is retrieved. The determination of the age with the use of carbon radioactive isotope study in the complex with the geostatistical interpolation techniques allowed creation age map of middle-Pliocene aquifer with high accuracy nad determination the recharge area on the north-east of the Mekong delta (South-Eastern area). From the recharge area, groundwater flows in the south-west direction at a flow velocity of 8 m/year and discharges into the sea (Siam Golf and Eastern sea). It is the first time by using geostatistical interpolation «cokriging» of two parameters (age - key parameter and depth of sampling - extra parameter). The tasks to improve the accuracy of specialized maps in Vietnam have been solved. The age map has been made with the correlation parameter 0,9, that justifies the high efficiency of the studies. Furthermore, results of the correlation between age and concentration chlorine of groundwater in the middle-Pliocene aquifer (n22) allowed making a suggestion, that formation of mineralized water is a result of mixing of meteoric water with the sedimentation waters of initial sea genesis, which were formed during Flandrian transgression which began about 21000 years ago and ended 4200 years ago.